Application of grafted cellulosic material as bioadsorbent for segregating of non-desirable content from waste water – A review. (2021) - Kumar, Maneesh; Gehlot, Praveen Singh; Parihar, Deepika; Surolia, Praveen K.; Prasad, Gayatri
Highlights: Grafted cellulose is reviewed in term of their adsorption demeanor. Grafting cellulose provides exceptional platform to non-desirable content (NDC). Water quality destroying contents of biosorption have been discussed. Biosorption feasibility's parameters are described. Abstract: In the recent era, the industrial activities are becoming more proficient in producing the domestic material, electrical appliances, pesticide, fertilizer, detergent, leather, dyes, medicine, rubber, plastics, and several cosmetic products. During the execution of this industrial purpose, numerous kinds of hazardous metals, dyes, pollutant, micro-pollutant, organic and inorganic fragment, carcinogenic and mutagenic components are being execrated and passed into water resources (river, pond, lake) in the bulk amount. The account of this, pure water turns into the contaminated water. To removing the non-desirable content (NDC) from water, the well-known cellulose and grafted cellulose are employed as a biosorbent. Chemically treated cellulose has better quality to hold the NDC over their backbone rather than untreated cellulose. The review paper fascinates the significant tendency of grafted cellulose to substantially adsorb the hazardous metal, dyes and other non-desirable product over their backbone. This review paper also enlightened the mechanism of biosorption on the bio-sample, and studied the biosorption-feasibility parameter in applied various conditions.